SUMBANGAN TEKS APOKALIPTIK TERHADAP GERAKAN SOSIAL POLITIK DALAM GEREJA - Yohanes Hasiholan Tampubolon (Institut Filsafat dan Teknologi Kreatif Ledalero, 2019)
Abstract: This article will identify apocalyptic texts in the Protestant canonical book and then explain about Martin Luther and Thomas Muntzer’s approach to apocalyptic texts. They see historical events from an apocalyptic perspective but contradict their application in social and political life. The author considers that apocalyptic texts are very influential in the socio-political movements that have been practiced by Muntzer and Luther. After seeing the approach and application of Muntzer and Luther to apocalyptic texts, the author explains the views of Marxist thinkers about the relationship of the Protestant reform movement and revolutionary theory.Keywords: movement, revolutionary, reformation, apocalyptic, Luther, Muntzer.